2009
DOI: 10.1002/cyto.a.20764
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of factors affecting the accuracy of results obtained when using flow cytometry in stem cell investigations: Where do you put your gates?

Abstract: Flow cytometry is used extensively in stem cell investigations but there is wide variation in the methods used for data analysis between laboratories. Data analysis can be challenging in stem cell biology as there is often no clear distinction between positive and negative populations. We have undertaken a critical appraisal of factors that affect the accuracy of results in stem cell applications. We used mouse embryonic stem cells and determined the expression of three common antigens in stem cell investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Indeed, in the study of Braun et al (13), accutase was used, whereas trypsin/EDTA was used in our study. Trypsin is a pancreatic serine protease, whereas accutase exhibits protease and collagenolytic activities (15). Interestingly, it has been reported that trypsin can cause removal and/or functional impairment of certain cell-surface membrane proteins Similar to CD105, the expression of CD73 on human MSC must exceed 95% according to the ISCT (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the study of Braun et al (13), accutase was used, whereas trypsin/EDTA was used in our study. Trypsin is a pancreatic serine protease, whereas accutase exhibits protease and collagenolytic activities (15). Interestingly, it has been reported that trypsin can cause removal and/or functional impairment of certain cell-surface membrane proteins Similar to CD105, the expression of CD73 on human MSC must exceed 95% according to the ISCT (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, many flow cytometric techniques have been developed for analyzing mature, nonadherent leukocytes, and therefore, some refinements are required when using stem cells (15). For example, the use of gating strategies is important not only to select the population of interest based on the selected markers but also to ensure an accurate analysis of the obtained data by excluding aggregates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis can be challenging in stem cell biology as there is often no clear distinction between positive and negative populations (27). In addition, expression levels of stem cell markers are also related with the method of cell isolation (28).…”
mentioning
confidence: 99%
“…In order to ensure an adequate number of observations, at least four million cells were evaluated for each liver specimen and characterized on the basis of more than one marker in order to improve the specificity of the detection (9,24).…”
Section: Discussionmentioning
confidence: 99%